Before This Night is Over - Solan, Peter; Rosinec, Vincent; Gýrová, Jana; Zelenohorská, Jitka; Danciak, Stano (Slovenský filmový ústav, 2013)
As the film's title suggests, the plot unfolds over the space of a few hours, and the location, a trendy nightclub, is just the right environment for this time of night. Peter Solan observes the social interaction of a handful of characters and, like the waitress moving about behind the bar, he switches from one patron to another, attempting to find out about their lives from snatches of their conversations. This might seem like an agreeable place to unwind, but the free-handed drunk at the bar, in a gesture of despair, fritters away his colleagues' wages; two office secretaries have come to the mountains in order to escape their tedious stereotypical lives, women caught in a rut despite their youth; and the two young guys attempting to chat them up are almost touching in their insecurity and clumsiness. Other tables are also occupied by an assortment of miserable-looking individuals ... The film is a prime example of the poetic charm of the 1960s New Wave, with its evocation of authentic atmosphere (here lightly melancholic and existentially dense), its gentle allusion instead of dramatic escalation, and its open ending. [www.kviff.com]
Keywords: DVD-Video